Analysis electrodynamic processes in induction inductor system with nonferromagnetic screen with use of magnetic pulse technology - Barbashova, M.; Shevtsov, V.; Барбашова, М. В.; Шевцов, В. В. (Харківський національний автомобільно-дорожній університет, 2014)
The theoretical study of cylindrical induction inductor system and the analysis of the radial density distribution of the induced currents, the Lorentz force, Ampere force and the force due to the magnetic properties of the workpiece in the system studied are presented.
Анализ электродинамических процессов в индукционной индукторной системе с неферромагнитным экраном при использовании магнитно-импульсных технологий
Аналіз електродинамічних процесів в індукційній індукторній системі з неферомагнітним екраном при використанні магнітно-імпульсних технологій
Keywords: induction inductor system; magnetic pulsed technology; индукционная индукторная система; магнитно-импульсные технологии; індукційна індукторна система; магнітно-імпульсні технології; 621.318